Cloud-computing based data integration for non-profit organization: web design and implementation - Yuwono Marta Dinata; Mychael Maoeretz Engel; Tony Antonio (International Journal of Computer and Information System (IJCIS), 2021)
Data is a very important part of our lives nowadays, but it requires a neat and systematic acquisition. This good and systematics data acquisition also required by non-profit institutions. Non-profit institutions in Indonesia are found within various fields, including health, arts, natural environment, agriculture, etc. One of the most needed data recording is the Indonesian Red Cross (PMI). PMI is engaged in the humanitarian field and has branches throughout Indonesia, including the districts. Donor data logging is one of the problems faced by PMI. Each time a donor does a blood donation, they need to rewrite their personal data on a piece of paper. This data will then be recapitulated into a computer which sometimes takes time and is not being inputted in real time. This system requires a change that makes data able to be inputted in real time and be stored properly and neatly. The data can then be stored in the cloud as well and be accessed in real time. For non-profit organizations such as PMI, this allows inputting and data processing to become more efficient and flexible. In this study, the System Development Life Cycle (SDLC) method was used, while the website uses the CodeIgniter (CI) framework. In this research, a website application is produced with features that are in accordance with the expected needs.